1995
DOI: 10.1128/mcb.15.11.6299
|View full text |Cite
|
Sign up to set email alerts
|

Novel NFAT Sites That Mediate Activation of the Interleukin-2 Promoter in Response to T-Cell Receptor Stimulation

Abstract: The transcription factors NFAT and AP-1 have been shown to be essential for inducible interleukin-2 (IL-2) expression in activated T cells. NFAT has been previously reported to bind to two sites in the IL-2 promoter: in association with AP-1 at the distal antigen response element at -280 and at -135. On the basis of DNase I footprinting with recombinant NFAT and AP-1 proteins, gel shift assays, and transfection experiments, we have identified three additional NFAT sites in the IL-2 promoter. Strikingly, all fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
181
3
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(191 citation statements)
references
References 72 publications
5
181
3
2
Order By: Relevance
“…Moreover, we had shown that Tpl-2 activates NFAT, a complex transcription factor composed of NFAT and AP1 components, whose activation is obligatory for IL-2 induction (Jain et al, 1992;Luo et al, 1996;Northrop et al, 1993;Rooney et al, 1995). Since Tpl-2 activates NFAT as well as the MAPK pathway (Ceci et al, 1997;Tsatsanis et al, 1998), which is required for the activation of AP1 (Jain et al, 1993), we examined whether dominant negative mutants of several proteins transducing signals along these pathways inhibit the activation of the IL-2 promoter by Tpl-2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we had shown that Tpl-2 activates NFAT, a complex transcription factor composed of NFAT and AP1 components, whose activation is obligatory for IL-2 induction (Jain et al, 1992;Luo et al, 1996;Northrop et al, 1993;Rooney et al, 1995). Since Tpl-2 activates NFAT as well as the MAPK pathway (Ceci et al, 1997;Tsatsanis et al, 1998), which is required for the activation of AP1 (Jain et al, 1993), we examined whether dominant negative mutants of several proteins transducing signals along these pathways inhibit the activation of the IL-2 promoter by Tpl-2.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of the IL-2 promoter relies on the simultaneous activation of the transcription factors NFAT, AP1, NF-kB and Oct (Figure 7a) (Garrity et al, 1994;Rooney et al, 1995). Of these, NFAT and NF-kB are obligatory for the activation of the IL-2 promoter.…”
Section: Tpl-2 Activates the Mapk Erk1 Via A Mek1-independent Pathwaymentioning
confidence: 99%
“…It has already been shown that Tat interacts with NFAT altering its transactivating capacity (20) and at present there is a controversy about the implication of NFAT in the regulation of the CD28RE/ AP1 response element (28,31). Therefore, it could be possible that the effects of Tat on this responsive element were caused by Tat-NFAT interaction, somehow altering the transactivating B-AP1 complex.…”
Section: Effect Of Tat On the Binding And Transcriptional Transactivamentioning
confidence: 99%
“…Thus, binding of NFAT proteins to B-like sites takes place on several promoters (20,(31)(32)(33). Moreover, NF-B and AP1 transcription factors are regulated not only by transcriptional and posttransductional mechanisms, but also by the qualitative composition of the dimers.…”
mentioning
confidence: 99%
“…1). The binding of AP-1 and NF-AT as well as Oct transcription factors controls both ARRE-1 and ARRE-2 (12)(13)(14)(15)(16)(17). Another important site within the IL-2 minimal promoter is a region that responds to CD28 costimulation, known as the CD28 response region (RR) (8,18,19) (see Fig.…”
Section: T He Generation Of T Cell-mediated Immune Responses Ismentioning
confidence: 99%